Resiliência em indivíduos com sequelas de acidente vascular encefálico - Lima , Raquel Janyne de (2017)
Introduction: The consequences arising from stroke cause several limitations in the functionality, affecting the biopsychosocial well-being of individuals, since many feel worthless because they depend of others to perform daily activities. Family and professionals should provide emotional support, encouraging behaviors that stimulate resilience in order to be able to better cope with this new condition. Objective: To evaluate the resilience levels of individuals with stroke sequelae in the municipality of João Pessoa/PB. Method: Exploratory, descriptive, cross-sectional and quantitative study, performed with 108 individuals with stroke sequelae registered in the Family Health Units of the municipality. The instruments were: socio-demographic and health instrument, Resilience Scale, Barthel Index and the Social Support Scale. The data were analyzed by the Statistical Package for Social Science version 22.0. The project was approved by the Research Ethics Committee of the Federal University of Paraíba under protocol n. 0641/15 and CAEE: 51438115.9.0000.5188. All ethical aspects of the National Health Council were attended. Results: Prevalence of participants aged 66-80 or over, women who lived with relatives, they had caregivers and received up to 880 reais as an individual monthly income. The majority presented moderate resilience, followed by low and high. There was a predominance of mild dependent individuals, followed by moderate dependents to perform daily activities. The majority of the participants of this research presented satisfactory social support. There was significant correlation between resilience and: self-reported health status, functional capacity and social support. Conclusion: It is hoped that this research will bring contributions for professionals who work directly with stroke victims, so that they receive appropriate assistance with their real needs and specificities, and with stimuli to resilient behaviors, especially in the Family Health Strategy.